Antiplatelet drugs: which targets for which treatments?. (June 2015) - Gachet, C.
Summary: The current standard care for acute coronary syndromes is dual antiplatelet therapy combining the COX1 inhibitor aspirin with a drug targeting the P2Y12 receptor, together with anticoagulation during and after early revascularization by percutaneous intervention. In very high‐risk patients, glycoprotein (GP) IIb/IIIa antagonists may also be used. Secondary prevention of ischemic events requires dual antiplatelet therapy for several months followed by lifelong low‐dose aspirin. The duration of treatment and the drugs to combine nevertheless remain matters of debate and the focus of ongoing research. Despite great progress, there is still room for improved efficacy and this could involve new targets for both antiplatelet drugs (like the thrombin receptor PAR1) and anticoagulants. However, improved efficacy is offset by an increased risk of bleeding. Stroke patients are still waiting for better treatment, their bleeding risk being particularly high. New targets including the collagen receptor, glycoprotein VI (GPVI), and the GPIb‐von Willebrand factor axis, governing platelet interaction with the diseased vessel wall, should enable us to complete the armamentarium of antiplatelet drugs.